Interactive Multimedia Development Based on Adobe Flash Cs6 on the Hazards of Free Association - Azharsyah, Al; Valianto, Budi; Novita, Novita; Kasih, Indra (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study aims to develop learning materials on the dangers of promiscuity through interactive multimedia based on Adobe Flash CS6 for class VIII students of SMPN 10 Langsa. This study uses the Brog & Gall development model. The results of the validation include two aspects of the assessment, namely the quality of the learning material by 97.2% then the content of the learning material obtains a result of 88.6 with very good criteria. The results of the feasibility of learning media validation by media design experts were declared "very good". The results of the validation include two aspects of the assessment, namely the aspect of the display of the learning media which obtained 90.9% with very good criteria, the programming aspect obtained very good results with a presentation of 91.7% with very good criteria. The results of the assessment carried out by five teachers obtained an average number of 85% with very good criteria. Then in the test of student responses to learning media in the form of interactive multimedia based on Adobe Flash CS6 which was developed, the results of each test were very good. In the small group test, the results obtained are 82.5% with good criteria, and the large group test results are 85.2% with very good criteria.